Characterization of water quality indicators in the municipality of La Unión, Lempira in Honduras (Nexo Revista Científica, 2021)
The objective of this work was to evaluate the water quality in the municipality of La Unión, Lempira in Honduras. Drinking water from the area was used as experimental material, with a test temperature of 190 C ± 20 C, using the methodology proposed by the National Technical Standard for Drinking Water Quality (1995). The results determined that the Water Quality Index (ICA) is 71.94 % ± 5.04 %, with an outlet flow of 0.156 m3/s and an inlet flow of 0.12 m3/s, generating a flow efficiency of 76.92 %, Furthermore, the physical and chemical parameters of the tests at different application points are within the permissible limits of this regulation. However, strains of fecal coliform were evident. Concluding that the water flow and the ICA are categorized as good, however, contamination was evidenced by the high number of coliforms, generating an alert about their consumption in the public health of this population.